1-year mortality in lung cancer in France according to key timepoints of care pathways. Issue 4 (28th November 2022) - Rivière, Axelle; Lecuyer, Anne Isabelle; Laurent, Emeline; Lefebvre, Carole; Lecomte, Thierry; Olivier, Elodie; Carmier, Delphine; Plantier, Laurent; Grammatico-Guillon, Leslie
Background: It is unclear whether delays in care affect prognosis of patients with lung cancer. The primary objective of this study was to describe the care pathway of patients diagnosed with lung cancer in a French region. Secondary objectives were to identify markers associated with 1) time from imaging to treatment and 2) with 1-year survival. Methods: In a retrospective cohort study, clinical data from multidisciplinary team meetings for all incident lung cancer cases discussed in 2018 in one French region were matched with medico-administrative data from the National Health Insurance Database. Care pathway time intervals were estimated for small cell lung cancer (SCLC), resected nonsmall cell lung cancer (NSCLC) and unresected NSCLC. Factors associated with delay in the care pathway were identified using linear regression; 1-year survival was analysed using Cox modelling. Results: A total of 685 patients were included. Median time between imaging and treatment was 49 days (interquartile range: 33–73), and was lower in cases of metastatic disease, SCLC and private care. At 1 year, 48% had died (resected NSCLC 12%). In unresected NSCLC, time from diagnostic imaging to first treatment <49 days was associated with a higher risk of death. Time intervals were similar in patients with squamous cell carcinoma versus adenocarcinoma or undifferentiated carcinoma. Discussion: Time intervals in the care pathways of lung cancer were similar to previous reports, confirming the robustness of retrospective databases. In unresectable NSCLC, rapid care was not associated with better survival. Care pathways of lung cancer were described with medico-administrative and clinical databases. In unresectable cases, rapid care access was not associated with better survival; the additional time for molecular biology did not impact treatment initiation. https://bit.ly/3qnArf0